School Operational Assistance Fund (BOS) Accounting Information System as an Internal Control Tool - Widati, Sindik; Setyawan, Wisnu; Riyanah, Sinah (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2023)
This study examines the accounting information system as an internal control tool over cash deposits and disbursements on the School Operational Assistance Fund or in Indonesian called Bantuan Operasional Sekolah (BOS). To enforce accountability and transparency in the use of the BOS Fund, which is one of the important sources of funds for education in Indonesia, it is very important to implement a strict monitoring mechanism. This research approach uses qualitative and descriptive research methods, which combine primary data collection, document analysis, interviews with stakeholders, and direct observation of the accounting information system that regulates the process of receiving and spending BOS funds. The framework includes elements of planning, in this case including the initial stage of making the RKAS, then implementation by carrying out the RKAS by procedures and paying attention to internal controls. Furthermore, the reporting stage leads to the realization of the RKAS, where all stages use an integrated information system. Based on the research results, SMK Darurrohman already has a computerized information system that is available to the public. This system is designed to receive and distribute BOS funds by the guidelines outlined in the BOS guidebook and adequate and accurate control mechanisms. Accounting information systems play a key role in supporting the implementation and maintenance of effective internal controls in an organization. Suggestions for the sustainability of BOS fund management for SMK Darurrohman Sukawangi include utilizing BOS to maintain and improve the quality and quantity of education, emphasizing routine, and implementing job rotation.